Analysis of sperm separation protocols for isolating cryopreserved human spermatozoa - Alena J Hungerford; Hassan W Bakos; Robert J Aitken (Bioscientifica, 2023)
Sperm cryopreservation is a valuable tool for the long-term preservation of male fertility. Thus, determining the optimal technique for isolating spermatozoa post-thaw is vital to ensure recovery of the highest quality spermatozoa with minimal iatrogenic damage. This not only enhances the chances of successful conception but also reduces the risk of genetic damage in the embryo. To address this issue, human semen samples were cryopreserved using a slow freezing protocol and Quinn's Advantage™ Sperm Freeze medium. The samples were subsequently thawed and subjected to three types of sperm isolation procedures: direct swim-up, density gradient centrifugation, and electrophoretic separation using the Felix™ device. Cryopreservation led to the anticipated loss of sperm motility and vitality in association with increases in lipid peroxidation and DNA damage. Following sperm selection, all three isolation techniques resulted in an increase in sperm motility which was particularly evident with the swim-up and Felix™ procedures. The latter also significantly improved sperm vitality. There were no differences between sperm separation techniques with respect to morphology, and mitochondrial reactive oxygen species generation remained essentially unchanged when cell vitality was taken into account. By contrast, major differences were observed in DNA integrity and lipid aldehyde formation, where Felix™ isolated cells exhibiting significantly less DNA damage than the other isolation procedures as well as lower levels of 4-hydroxynonenal formation. Electrophoretic sperm isolation, therefore, offers significant advantages over alternative separation strategies, in terms of the quality of the gametes isolated and the time taken to achieve the isolation.